Using the market to address climate change: Insights from theory and experience - Joseph E. Aldy; Robert N. Stavins (Fondazione Eni Enrico Mattei (FEEM), 2011)
Emissions of greenhouse gases linked with global climate change are affected by diverse aspects of economic activity, including individual consumption, business investment, and government spending. An effective climate policy will have to modify the decision calculus for these activities in the direction of more efficient generation and use of energy, lower carbon-intensity of energy, and - more broadly - a more carbon-lean economy. The only approach to doing this on a meaningful scale that would be technically feasible and cost-effective is carbon pricing, that is, market-based climate policies that place a shadow-price on carbon dioxide emissions. We examine alternative designs of three such instruments - carbon taxes, cap-and-trade, and clean energy standards. We note that the U.S. political response to possible market-based approaches to climate policy has been and will continue to be largely a function of issues and structural factors that transcend the scope of environmental and climate policy.
Keywords: Q54; Q58; Q40; Q48; 330; Global Climate Change; Market-Based Instruments; Carbon Pricing; Carbon Taxes; Cap-And-Trade; Clean Energy Standards